Influence of chitosan coatings with rosemary essential oil on mechanical and physical properties of packaging paper - Vrabič Brodnjak, Urška; Tihole, Katarina (Journal of Graphic Engineering and Design, 2020)
Recently, coated paper substrates have been used in a wide range of packaging applications. In this research, we present a chitosan with rosemary essential oil, paper coating as water and possible repellent resistant solution on biological basis. The aim of this research was to coat two different uncoated (also calendared) papers with a bio-based coating solution and to analyse mechanical, physical properties, resistance of coating and print ink. The resulting coated chitosan-rosemary oil, papers showed remarkable water resistance (Cobb60 values 5.18 and 4.55 g/m2). The good mechanical properties of the coated papers increased after the coating treatment. Namely, elongation at break and tear strength improved due to the structure of the coating itself. The resistance of coatings on printed surfaces also showed sufficient results for further packaging applications.